Physical and chemical processes driven by natural iron minerals in aquatic environments - Yuanyuan Chen; Na Huang; Yingying Li; Yin Lu; Yilan Jiang; Zeng Zhou; Dawei Wang (Water Cycle)
In aquatic environments, natural iron minerals are a prevalent form of iron, which alter substance speciation through adsorption and redox reactions. Their abiotic migration and transformation processes are pivotal for maintaining aquatic ecosystem stability, particularly in nitrogen and organic carbon dynamics. Recent studies have been revealed that the generation of reactive oxygen species at iron mineral-redox fluctuation interfaces can change the transformations of pollutants and organic carbon. This article provides a concise introduction to the characteristics, extraction, and characterization of natural iron minerals in aquatic environments, and summarizes their predominant abiotic processes. These conclusions are expected to provide new insights into a deeper understanding of water dynamics that are influenced by natural iron minerals.